Martin Luther and his Schmalkaldic Confession - Spehr, Christopher (Vox Scripturae - Revista Teológica Internacional, 2018)
The present study provides an outline of the history of the emergence of the Smalcalde Articles in the context of the discussions of the Smalcalde League on the position of Protestants in view of the announcement of a council in Mantua. In a second moment, it briefly presents the content of the Articles of Smalcalde, which appear in a form that oscillates between Luther’s private confession and public doctrinal document. It then presents the discussions that culminated in the fact that Luther’s articles were not officially accepted by the League of Esmalcalde in 1537. Finally, he presents the various historical aspects that are relevant around the publication and reception of Luther’s Articles of Esmalcalde, which culminated, in the end, in the reception of these articles in the Book of Concord, as Confessional Writing of the Lutherans.
Keywords: Smalcalde Articles; Confession of faith; Theology of Martin Luther; League of Esmalcalde